Extermínio cultural como violação de direitos humanos: o contexto criminal do etnocídio e seu desenvolvimento no campo do saber jurídico-penal. - Vieira, Gustavo José Correia (2011)
The following study addresses about the ethnocide, a form of violence that has its own characteristics. In short, it is seeking to enter into a discussion and legal-criminal from the standpoint of human rights how this practice is materialized, and what it seeks to eliminate. Throughout this study, are considered as certain basic anthropological concepts to understand this phenomenon, mainly around the concept of cultural identity, which is linked with corporeality and is responsible for production, reproduction and development of human life, on a community level. Also it considers it its relationship with colonialism, but also traces an analysis of the conditions of vulnerability and potential victim characteristics present in the achievement of ethnocide. Finally, the study proposed here is developed in a legal context, in comparison of ethnocide with other forms of human rights violation, resulting in an approach on the importance of the right of the people and its elements (ethics, memory and recognition) as a parameter for the prevention of ethnocide.